Nondestructive analysis of pitting corrosion characteristics on EN AW-2024-T3 using 3D optical pattern profilometry. (3rd April 2018) - Schmidl, E.; Pippig, R.; Morgenstern, R.; Lampke, T.; Scharf, I.
ABSTRACT: High-strength age-hardenable aluminium alloys are susceptible to localised corrosion. It is vital to monitor the evolution of the corrosion depth in order to prevent a critical degradation of the mechanical properties. This study presents the application of 3D optical pattern profilometry for the analysis of the pitting corrosion behaviour of the aluminium alloy EN AW-2024-T3. Therefore, measurements were conducted using a 1 M NaCl solution at different exposure times. The measurements are compared to the results of optical microscopy investigations of metallographic specimens as well as laser scanning microscopy measurements. In immersion bath tests, the 3D pattern profilometry shows a high measurement accuracy of the pitting corrosion. Regarding the pit characteristics, corroded metal sheets exhibit an increase in the pit depth, volume and area with an increasing exposure time of up to 312 h and then decrease. Moreover, a higher increase in the width in rolling direction than perpendicular to it is noticeable.